KONSEP KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA MUTU AKADEMIK RELIGIUS - Muhammad Hasyim, Muhammad Husni dan (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2017)
This view of the quality of education is now very diverse. Society perceives quality education is a luxury building school have, and school beautiful garden. This research method using descriptive qualitative research. The goal is to analyze and find the concept of academic quality religious culture developed by Principals. The results of the research that the concept of quality culture developed through the habit of behaving in everyday life. The findings of the research that developed the concept of quality culture is a collective agreement that puts the Islamic culture.